2000
DOI: 10.1161/01.res.87.12.e61
|View full text |Cite
|
Sign up to set email alerts
|

Independent Signals Control Expression of the Calcineurin Inhibitory Proteins MCIP1 and MCIP2 in Striated Muscles

Abstract: Calcineurin, a calcium/calmodulin-regulated protein phosphatase, modulates gene expression in cardiac and skeletal muscles during development and in remodeling responses such as cardiac hypertrophy that are evoked by environmental stresses or disease. Recently, we identified two genes encoding proteins (MCIP1 and MCIP2) that are enriched in striated muscles and that interact with calcineurin to inhibit its enzymatic activity. In the present study, we show that expression of MCIP1 is regulated by calcineurin ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
303
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(326 citation statements)
references
References 38 publications
18
303
0
5
Order By: Relevance
“…4k) and protein (Supplementary Fig. 9d) expression, indicating excessive activation of calcineurin/NFAT signalling in Myoscape KO hearts in response to increased biomechanical stress32. Consistently, Myoscape KO mice showed enhanced fibrosis after aortic constriction, as shown by sirius red stainings of heart sections (Supplementary Fig.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…4k) and protein (Supplementary Fig. 9d) expression, indicating excessive activation of calcineurin/NFAT signalling in Myoscape KO hearts in response to increased biomechanical stress32. Consistently, Myoscape KO mice showed enhanced fibrosis after aortic constriction, as shown by sirius red stainings of heart sections (Supplementary Fig.…”
Section: Resultssupporting
confidence: 54%
“…Despite decades of research, heart failure remains a major cause of death and mortality32333435363738. Therefore, improved understanding of the molecular mechanisms underlying heart failure is still urgently needed to develop novel targeted treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…AKAP79, cain/cabin 1, and CBHP are ubiquitous factors and were found to inhibit NFAT function or translocation to the nucleus (Crabtree, 2001). More recently, two additional endogenous calcineurin-specific inhibitors (DSCR1/MCIP1 and ZAKI-4/DSCR1L1/MCIP2), highly expressed in striated muscles and brain, were found (Yang et al, 2000;Rothermel et al, 2001). DSCR1 expression is induced by calcineurin and hence forms a negative feedback loop to limit calcineurin activation Signalling and pathways in molecular determination of skeletal muscle phenotype (Yang et al, 2000).…”
Section: Fibre Types: Coordinated Isoform-specific Expressionmentioning
confidence: 99%
“…More recently, two additional endogenous calcineurin-specific inhibitors (DSCR1/MCIP1 and ZAKI-4/DSCR1L1/MCIP2), highly expressed in striated muscles and brain, were found (Yang et al, 2000;Rothermel et al, 2001). DSCR1 expression is induced by calcineurin and hence forms a negative feedback loop to limit calcineurin activation Signalling and pathways in molecular determination of skeletal muscle phenotype (Yang et al, 2000). Its over-expression in transgenic mice prevented cardiac hypertrophy Van Rooij et al, 2004).…”
Section: Fibre Types: Coordinated Isoform-specific Expressionmentioning
confidence: 99%
“…SRF also enhances the hypertrophic process in muscle fibers 81,82) . For example, the authors showed that, in mechanically overloaded rat muscles, SRF protein is coing particularly abundant in slow-twitch muscle, but not detectable in fast-twitch glycolytic muscles 54,55) . More recently, reporter assays using cultured myoblasts indicated that the transcriptional activation of NFAT by calcineurin was also inhibited by calsarcin-2 56) .…”
Section: Insulin-like Growth Factor-i and Mapk (Proliferation Phase)mentioning
confidence: 99%